THE WEAK ASPECTS OF THE INDUSTRIAL DESIGN PROTECTION SYSTEM IN INDONESIA - Noerhadi, Cita Citrawinda (UI Scholars Hub, 2013)
Industrial property is is being used by an increasing number of developing countries as an important tool of technological and economic development. Developing countries have also been made aware that it is in their best interest to establish national industrial property systems. Indonesia as a signatory member of the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO), Indonesia has enacted Law No. 31 of 2000 concerning Industrial Design on 20 December 2000. Since the enactment of Law No. 31 of 2000 several cases have occurred and been brought before the Commercial Court involving the cancellation of lawsuits with regard to issues of the lack of ‘novelty’ of an industrial design which have already been granted to other people. There are several weak aspects of Law No. 31 of 2000 which in practice can create legal uncertainty and may potentially cause a barrier towards the effectiveness of the implementation of Law No. 31 of 2000.